Pendekatan Diagnosis Holistik Pasien Asma Melalui Pendekatan Dokter Keluarga di Puskesmas Ulee Kareng - Nur Ikhsani Rahmatika; Intan Nabilla Ayuni; Nabila Azhara (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Asthma is a chronic disease that interferes with the airway due to inflammation and swelling of the walls in the airways so that becomes very sensitive to the entry of foreign objects which cause an overreaction. Based on data from the Ministry of Health for 2020, the number of asthma sufferers in Indonesia is 4.5% of the total population of Indonesia or as many as 12 million more. Meanwhile, based on Aceh Health Service in 2022, it was noted that Asthma sufferers in the Banda Aceh area has reached 11,534 cases. This study is a case report study with data obtained through autoanamnesis, physical examination, home visit to complete family data, psychosocial, and environmental data. Patient Mrs. NS, 51 years old, came with complaints of coughing and a runny nose for 3 days before coming to the Ulee Kareng Health Center, occasionally the patient coughed to the point of causing chest pain. The patient already has a history of asthma since elementary school. The application of family doctor services to asthma patients is necessary to prevent acute exacerbations and prevent the occurrence of asthma in the patient's family.